Avaliação do modelamento da propagação de ondas sísmicas pelo método lowrank - Landeta Bejarano, Andres Valentino, 1995- (2022)
Orientadores: Maria Amélia Novais Schleicher, Joerg Dietrich Wilhelm Schleicher